2015
DOI: 10.1007/s10482-015-0380-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus acidophilus dietary supplementation on the performance, intestinal barrier function, rectal microflora and serum immune function in weaned piglets challenged with Escherichia coli lipopolysaccharide

Abstract: This study was conducted with a lipopolysaccharide (LPS)-challenged piglet model to determine the effects of diets containing Lactobacillus acidophilus on the performance, intestinal barrier function, rectal microflora and serum immune function. A total of 150 piglets (initial body weight (BW) 7.53 ± 0.21 kg) were allotted to one of the following diets, including a basal diet, a basal diet supplemented with 250 mg/kg Flavomycin, or basal diet plus 0.05, 0.1 or 0.2 % L. acidophilus. On day 28 of the trial, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 38 publications
4
33
0
Order By: Relevance
“…In the present study, the results indicated that piglets fed 5 Â 10 10 CFU L. acidophilus or 3000 mg ZnO/kg feed had greater ADG, lower F:G than the unsupplemetend group. Consistently, previous studies have established improved ADFI and ADG of piglets fed Lactobacillus strains (Lee et al 2012;Yang et al 2014;Qiao et al 2015) or ZnO (Hill et al 2001). Thus, we can speculate that both LA and ZnO could improve the growth and might partly attenuate the effects of the stress of piglets during the post-weaning period.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the present study, the results indicated that piglets fed 5 Â 10 10 CFU L. acidophilus or 3000 mg ZnO/kg feed had greater ADG, lower F:G than the unsupplemetend group. Consistently, previous studies have established improved ADFI and ADG of piglets fed Lactobacillus strains (Lee et al 2012;Yang et al 2014;Qiao et al 2015) or ZnO (Hill et al 2001). Thus, we can speculate that both LA and ZnO could improve the growth and might partly attenuate the effects of the stress of piglets during the post-weaning period.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, Lactobacillus strains would synthesise exopolysaccharides in their growth phase (Lebeer et al 2008). In our previous study, we have proved that L. acidophilus could modify intestinal microflora (Qiao et al 2015), which may be important to enhance health state of piglets. Previous studies reported that the breakdown of intestinal barrier function was the deleterious effect of weaning (Spreeuwenberg et al 2001;Boudry et al 2004).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Lactobacillus rhamnosus JB-1) [17]. In parallel, swine-based models also highlight the critical role of the GI microbiota and bacterial supplementation in enhancing immune development and functioning [18][19][20][21][22][23][24][25][26]. These data include evidence of altered immune development and function in differentially-raised (conventional vs. isolator) newborn [18,19] and GF piglets [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Butyrate) and branched chain fatty acids [22], (b) reduced concentrations of Clostridium and increased concentrations of Lactobacillus [22,23], (c) improved immune functioning [22,24], (d) greater antioxidant activity [25], and (e) reduced expression of proteins linked to the stress response [26] following supplementations with Lactobacillus fermentum I5007 [22,25,26], Lactobacillus delbrueckii subsp. bulgaricus 2038 [23], and Lactobacillus acidophilus [24].…”
Section: Introductionmentioning
confidence: 99%